HUBUNGAN TINGKAT PENDIDIKAN DAN MOTIVASI ORANGTUA DENGAN PRESTASI BELAJAR FIQH SISWA - Samiran; Abdul Rouf; Muhtadi (FAI- Undar, 2017)
The relationship between Parent Education and Motivation on Student Achievement of Fiqh. There are many people who argue that to achieve high academic achievement necessary intellectual intelligence (IQ) is also high. However, according to recent research in the field of psychology to prove that IQ is not the only factor that affects one's learning achievement, but there are many other factors that influence environmental factors include family yabg between dimensions is the level of parental education and motivation.The purpose of this study was to determine whether there is a relationship between level of education and motivation parents with student achievement of Fiqh. Alternative hypothesis (Ha) in this study is that there is a relationship between level of education and motivation of parents with student achievement nil hypothesis (Ho) is no relationship between the level of parental education and motivation to student achievement. The independent variable in this study is the level of parent and Motivation penidikan parents while learning achievement as a dependent variable. The population in this study were students of class VIIin Islamic Junior State School of Saradan Madiun of a total of 183 students. The study sample was 40 students, using proportional random sampling method.Data collection and Motivation parental educational level of parents is done with the questionnaire, and to measure student achievement used method of examination of documents by looking at grades. Correlation analysis with the formula of Pearson Product Moment correlation ranged from 0.140 to 0.847 and r = 0235 tables. Based on the significant level of 0.05 was obtained 38 valid items and 2 items fall of 40 items. Value of 0.908 obtained reliability coefficient was calculated with Cronbach alpha formula. The results of the analysis of research data shows correlation coefficient of -1.23 (> 0.05) then Ho is rejected and Ha accepted. Conclusions from this research that there is a relationship between the level of parental education and motivation of parents with student achievementof Fiqh in Islamic Junior State School of Saradan Madiun